1999
DOI: 10.1042/cs19980111
|View full text |Cite
|
Sign up to set email alerts
|

Sustained elevation of plasma brain natriuretic peptide levels associated with progressive ventricular remodelling after acute myocardial infarction

Abstract: Previous studies have shown that levels of plasma brain natriuretic peptide (BNP) increase in an early phase of acute myocardial infarction. However, the relations between plasma BNP levels and left ventricular remodelling, which occurs long after acute myocardial infarction, are not fully understood. Venous plasma BNP levels were measured 2, 7, 14, 30, 90 and 180 days after the onset of acute myocardial infarction in 21 patients. Left ventricular end-diastolic volume index (EDVI, ml/m2) in acute (5 days) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Giallauria et al [21,28], showed a decrease of NT-proBNP circulating levels after three months of moderateintensity aerobic training, in patients with ventricular dysfunction after MI. Our data show that moderate-intensity aerobic training does not interfere with the natural course of NT-proBNP plasma level decrease, which usually occurs in the context of MI, associated to VR, as reported by Nagaya et al [29].…”
Section: Discussionsupporting
confidence: 64%
“…Giallauria et al [21,28], showed a decrease of NT-proBNP circulating levels after three months of moderateintensity aerobic training, in patients with ventricular dysfunction after MI. Our data show that moderate-intensity aerobic training does not interfere with the natural course of NT-proBNP plasma level decrease, which usually occurs in the context of MI, associated to VR, as reported by Nagaya et al [29].…”
Section: Discussionsupporting
confidence: 64%
“…Finally, it is possible that myocardial infarction is simply an initial trigger for the release of BNP, as has been observed in other settings. [22][23][24][25] The elevation of BNP in outpatients with inducible ischemia has implications for the use of BNP as a diagnostic test for systolic dysfunction. Many (including the European Society of Cardiology) have proposed that BNP should be used as a first-line test for patients with symptoms suggestive of ventricular dysfunction, particularly high-risk patients such as those with coronary disease.…”
Section: Discussionmentioning
confidence: 99%
“…We also measured plasma brain natriuretic peptide (BNP) levels as the referential serological indicator of LV dysfunction, 17,18 long-term prognosis, [19][20][21] and LV remodeling after MI. [21][22][23] …”
Section: Introductionmentioning
confidence: 99%